Tau phosphorylation‐associated spine regression does not impair hippocampal‐dependent memory in hibernating golden hamsters. Issue 3 (13th October 2015) - Bullmann, Torsten; Seeger, Gudrun; Stieler, Jens; Hanics, János; Reimann, Katja; Kretzschmann, Tanja Petra; Hilbrich, Isabel; Holzer, Max; Alpár, Alán; Arendt, Thomas
ABSTRACT: The microtubule‐associated protein tau, in its hyperphosphorylated form, is the major component of paired helical filaments and other aggregates in neurodegenerative disorders commonly referred to as "tauopathies". Recent evidence, however, indicates that mislocalization of hyperphosphorylated tau to subsynaptic sites leads to synaptic impairment and cognitive decline even long before formation of tau aggregates and neurodegeneration occur. A similar, but reversible hyperphosphorylation of tau occurs under physiologically controlled conditions during hibernation. Here, we study the hibernating Golden hamster (Syrian hamster, Mesocricetus auratus ). A transient spine reduction was observed in the hippocampus, especially on apical dendrites of hippocampal CA3 pyramidal cells, but not on their basal dendrites. This distribution of structural synaptic regression was correlated to the distribution of phosphorylated tau, which was highly abundant in apical dendrites but hardly detectable in basal dendrites. Surprisingly, hippocampal memory assessed by a labyrinth maze was not affected by hibernation. The present study suggests a role for soluble hyperphosphorylated tau in the process of reversible synaptic regression, which does not lead to memory impairment during hibernation. We hypothesize that tau phosphorylation associated spine regression might mainly affect unstable/dynamic spines while sparing established/stable spines. © 2015 Wiley Periodicals, Inc.